GAYA BAHASA KOMENTATOR SEPAK BOLA DALAM ACARA INDONESIA SUPER LEAGUE DI STASIUN TELEVISI ANTV - Mardiansyah, Doni; Ermanto, Ermanto; Amir, Amril (Universitas Negeri Padang, 2012)
The purpose of this article is to describe the form of a style that is used by soccer commentators in the Indonesian Super League event on television quiz on sentence structure and meaning based on whether or not direct. The data of this study is the speech that contain language style. Source of research data is broadcast live football matches Indonesia Super League during the month of April 2012 in television quiz. Data was collected using recording techniques and assisted with the recording sheet. The study's findings: (1) style language is based on the sentence structure is found as many as three of style, a style that is the climax, antithesis, and repetition. (2) style language is based on direct or absence of meaning is found as many as 14 styles of language, namely alliteration, asonansi, asindeton, euphemism, hyperbole, oxymoron, erotesis, simile, metaphor, personification, eponymous, sinekdoke, antonomasia, and irony. Â Kata kunci: gaya bahasa, komentator,